A comparative study of sclerotherapy and rubber band ligation versus open hemorrhoidectomy in second degree hemorrhoids - Ammanagi, Amit Shivshankar; Mathew, Tony (International Surgery Journal, 2019)
Background: Hemorrhoids affects the quality of life and leads to significant pain and discomfort. The current study was done to evaluate the results of comparative treatment of rubber band ligation, sclerotherapy and open hemorrhoidectomy. Methods: This was a prospective study done on 90 patients with second grade internal hemorrhoids attended to the Department of General Surgery at S. Nijalingappa Medical and Research Centre, Bagalkot during the study period from 2012 November to 2013 December. Systemic examination and basic investigations were done. According to severity and type of symptoms, patients are subjected for open hemorrhoidectomy (n=30), banding (n=30) and sclerotherapy (n=30). Results: Occurrence of hemorrhoids was seen between the age group of 36 to 45 years. Out of 90 patients 52 were males and 38 were females. Common presenting complaint was bleeding per rectum and mass per rectum in 33.33% of patients. Postoperative hospital stay was 1 day in the groups treated with rubber band ligation and sclerotherapy and in open hemorrhoidectomy 28 patients stayed for 3 days and 2 patients for 5 days. About 70% of patients belonging to rubber band ligation and sclerotherapy group gave excellent response to the same. Conclusions: In our study, rubber band ligation technique was found to be more cost effective and reliable to treat second grade hemorrhoids with lesser postoperative complications followed by sclerotherapy and hemorrhoidectomy.